2008
DOI: 10.1177/1073191107312611
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity and Obsessive—Compulsive Disorder

Abstract: Anxiety sensitivity (AS), a cognitive risk factor for anxiety disorders, was evaluated in a homogeneous obsessive-compulsive disorder (OCD) sample. A total of 280 individuals with OCD completed measures. Evaluation of the Anxiety Sensitivity Index revealed a latent structure that was congruent with previous studies showing a single higher order and three lower order factors, although greater variance was accounted for by the general factor than in a previous study. AS was significantly associated with OCD symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 49 publications
(77 reference statements)
4
41
0
Order By: Relevance
“…Similar results were found in a longitudinal study of adolescents (Hayward, Killen, Kraemer, & Taylor, 2000;Hayward, Killen, & Taylor, 2003;Hayward & Wilson, 2007;Schmidt, Zvolensky, & Maner, 2006). Studies also report a significant relationship between AS and other anxiety disorders, such as OCD and social phobia (Anderson & Hope, 2009;Calamari et al, 2008;Rector, Szacun-Shmizu, & Leybman, 2007). Further studies demonstrate that apart from various anxiety disorders, AS facilitates the development of other anxiety-related behaviors.…”
Section: Anxiety Sensitivity Theorysupporting
confidence: 81%
“…Similar results were found in a longitudinal study of adolescents (Hayward, Killen, Kraemer, & Taylor, 2000;Hayward, Killen, & Taylor, 2003;Hayward & Wilson, 2007;Schmidt, Zvolensky, & Maner, 2006). Studies also report a significant relationship between AS and other anxiety disorders, such as OCD and social phobia (Anderson & Hope, 2009;Calamari et al, 2008;Rector, Szacun-Shmizu, & Leybman, 2007). Further studies demonstrate that apart from various anxiety disorders, AS facilitates the development of other anxiety-related behaviors.…”
Section: Anxiety Sensitivity Theorysupporting
confidence: 81%
“…Calamari, Rector, Woodard, Cohen, and Chik (2008) found that anxiety sensitivity (AS; i.e., the fear of anxiety-related bodily sensations) contributed to models predicting OCD severity, beyond the cognitive appraisal constructs described above. The same study found that the relationship between AS and OCD symptom severity varied across symptom dimensions.…”
Section: Emotions In Ocdmentioning
confidence: 94%
“…Several trait-like vulnerability factors that have been linked to both posttraumatic stress (Engelhard et al, 2010; Monson, Price, Rodriquez, Ripley, & Warner, 2004; Taylor, 2003) and OC symptoms (Calamari, Rector, Woodard, Cohen, & Chik 2008; Olatunji et al, 2007) were examined for appropriateness of inclusion as covariates to increase confidence that significant associations are due to hypothesized variables and not relevant third variables.…”
Section: Methodsmentioning
confidence: 99%